Perencanaan Arsitektur Sistem Informasi dan Teknologi Informasi pada Universitas Ottow Geissler Papua Menggunakan Enterprise Architecture Planning (EAP) - Yohan Maurits Indey; Kristoko Dwi Hartomo; Irwan Sembiring (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The development of Information Systems and Technology has caused a change in the role of efficiency and effectiveness into a strategic and rapid competitive role in the most important educational institutions at the Higher Education level which are managed by non-governmental organizations (private), system support and information technology in the main activities in Higher Education are very important. needed. In business processes that are less than optimal often cause obstacles in the application of information systems, changes often occur individually or in organizations that result in negative responses or rejections that hinder business processes. Information system planning in higher education can be realized in the form of a blueprint. Enterprise Architecture Planning (EAP) is a process of defining architecture for using information in order to support the implementation of business processes and planning for the architecture, as well as to create blueprints for academic information systems in universities that contain various data, application and technology architectures.